(untitled) (Journal of Legal Studies, 2024)
Just over a decade ago, public tertiary institutions depended on the government for funding and received instructions on running their day-to-day affairs from the state. Recently, GIMPA a public tertiary institution deployed legal options to gain autonomy to stabilize its financial performance and service delivery. This article updates the progress that has since been made in understanding the reversal of the stressful financial situation of the institute through the lens of the existing legal framework. Further, the paper examined an ambitious organizational structure dwelling on a robust legal framework to redirect management policies, rules, regulations, and functional decisions of a public tertiary institution serving public management and public administration training and consultancy. Termed “legal framework,” this set of legal instruments is cultivated into efficient and effective operations that yield financial stability that ensures growth and is trajected towards national development.